2008
DOI: 10.2174/156652408784221289
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death by Necrosis, a Regulated Way to Go

Abstract: Apoptosis is a programmed form of cell death with well-defined morphological traits that are often associated with activation of caspases. More recently evidence has become available demonstrating that upon caspase inhibition alternative programs of cell death are executed, including ones with features characteristic of necrosis. These findings have changed our view of necrosis as a passive and essentially accidental form of cell death to that of an active, regulated and controllable process. Also necrosis has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 245 publications
(331 reference statements)
0
59
0
1
Order By: Relevance
“…Treatment of isolated macrophages activated in vivo in mice with apoptosis-inducing agents lead to a dramatic increase in Caveolin-1 levels while Caveolin-2 is not affected. Phosphatidylserine (PS) externalization is considered a defining feature associated with apoptosis [111]. Interestingly, Caveolin-1 is present in lipid rafts and colocalizes with PS at the cell surface of apoptotic macrophages, where it is suggested to be involved in the efficient externalization of PS [112].…”
Section: Caveolin-1 and Apoptosismentioning
confidence: 99%
“…Treatment of isolated macrophages activated in vivo in mice with apoptosis-inducing agents lead to a dramatic increase in Caveolin-1 levels while Caveolin-2 is not affected. Phosphatidylserine (PS) externalization is considered a defining feature associated with apoptosis [111]. Interestingly, Caveolin-1 is present in lipid rafts and colocalizes with PS at the cell surface of apoptotic macrophages, where it is suggested to be involved in the efficient externalization of PS [112].…”
Section: Caveolin-1 and Apoptosismentioning
confidence: 99%
“…These organelles are the predominant sites for intracellular calcium stores, and the highly organized subcellular architecture of adult cardiac myocytes enforces close proximity between SR and mitochondria, making it possible for calcium to transfer from SR to mitochondria through junctional microdomains referred to as 'calcium hot-spots' (Rizzuto and Pozzan, 2006). Calcium delivery to mitochondria and uptake by the calcium uniporter are a potent stimulus for mitochondrial permeability transition (MPT) in the heart and elsewhere, and the resulting inner and outer membrane rupture leads to cell death from ATP depletion, called 'programmed necrosis' (Nakayama et al, 2007;Henriquez et al, 2008). The Dorn group found that there is a direct relationship between NIX/BNIP3L level in NIX/BNIP3L-overexpressing and -knockout mice and SR calcium content, suggesting that ER/SRlocalized NIX/BNIP3L can affect intracellular calcium stores in a similar manner as previously reported for BCL2 and BAX (Foyouzi-Youssefi et al, 2000;Nutt et al, 2002;Scorrano et al, 2003).…”
Section: Transgenic Cardiac Overexpression Studies Of Bnip3 and Nix/bmentioning
confidence: 99%
“…Prominent features of necrosis are ATP depletion, loss of ion homeostasis and membrane polarity leading to rapid swelling of the cell, membrane rupture, and subsequent release of cellular contents. Necrosis is neither organized nor executed in a similar manner to apoptosis, and cell death is a consequence of irreparable damage (Henriquez et al ., 2008). Necrosis therefore frequently occurs during pathological conditions including stroke, ischemia, and neurodegenerative disorders (Syntichaki et al ., 2002; Malhi et al ., 2006; Henriquez et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Necrosis is neither organized nor executed in a similar manner to apoptosis, and cell death is a consequence of irreparable damage (Henriquez et al ., 2008). Necrosis therefore frequently occurs during pathological conditions including stroke, ischemia, and neurodegenerative disorders (Syntichaki et al ., 2002; Malhi et al ., 2006; Henriquez et al ., 2008). Inflammation is associated with necrosis and not with apoptotic cell death (Scaffidi et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%